Quantitative Techniques for Competition and Antitrust Analysis - Davis, Peter J. (Peter John), 1970-; Garces, Eliana, 1968- (Book collections on Project MUSE., 2010)
This book combines practical guidance and theoretical background for analysts using empirical techniques in competition and antitrust investigations. Peter Davis and Eliana Garces show how to integrate empirical methods, economic theory, and broad evidence about industry in order to provide high-quality, robust empirical work that is tailored to the nature and quality of data available and that can withstand expert and judicial scrutiny. Davis and Garces describe the toolbox of empirical techniques currently available, explain how to establish the weight of pieces of empirical work, and make s.